Self-perception of a clinical teaching method and satisfaction of medical students from a public university - Fernández-Villacorta, Freddy Javier (2024)
Objetive: To determine the relationship between the self-perception of the SNAPPS method and the level of satisfaction of the medical student of a public university in Trujillo 2020 - 2021. Methods: the cross-sectional, retrospective correlational descriptive work evaluated 190 students enrolled in the years 2020 and 2021 in the 5th year of medicine at the National University of Trujillo through a virtual form. Results: The average age was 24.42 years (21-42 years). 59.5% were male, and the majority were men with 59.5%. The dimension of the highest level in the self-perception of the SNAPPS method was in skills, collaboration and virtual support and resources. Regarding the dimension of student satisfaction, it was average in teaching, student expectations and quality of the institution. When relating both variables, we found a strong association between them. Conclusion: There is a strong relationship between the self-perception of the SNAPPS method and the level of satisfaction of the medical student at the National University of Trujillo.